2022
DOI: 10.1002/pat.5838
|View full text |Cite
|
Sign up to set email alerts
|

Study on catechol/tetraethylenepentamine and nano zinc oxide co‐modifying ultrahigh molecular weight polyethylene fiber surface to improve interfacial adhesion

Abstract: To improve interfacial adhesion to rubber matrix, a lower cost surface modification strategy of ultrahigh molecular weight polyethylene (UHMWPE) fiber was proposed by replacing expensive dopamine with the two‐component system of catechol/tetraethylenepentamine (CAT/TEPA) and then depositing nano zinc oxide (ZnO NPs). By Michael addition reaction or Schiff base reaction between CAT and TEPA, the CAT/TEPA layer was coated on the fiber surface, and further served as a secondary functional platform to realize ZnO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…As shown in Figure and Table S1, with the increase in the amount of the SiC filler, the tensile strength (σ) and elongation at break ( E b ) for the SiC/NR composites decreases. The imperfect interfacial interaction between the rigid SiC and soft NR chains results in the formation of defects and voids in the NR composites, thereby limiting the mobility of the polymer chains . On the other hand, the weak interaction between SiC and NR leads to stress accumulation in the composites, resulting in lower values of σ and E b than those of pure NR.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure and Table S1, with the increase in the amount of the SiC filler, the tensile strength (σ) and elongation at break ( E b ) for the SiC/NR composites decreases. The imperfect interfacial interaction between the rigid SiC and soft NR chains results in the formation of defects and voids in the NR composites, thereby limiting the mobility of the polymer chains . On the other hand, the weak interaction between SiC and NR leads to stress accumulation in the composites, resulting in lower values of σ and E b than those of pure NR.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, aramid 3D braided composites were modified by the chemical reaction of CA/PGPA on the AF surface. CA/PGPA was oxidized, polymerized, and co‐deposited on the surface of the fiber to introduce reactive groups on the fiber surface and improve the interfacial interaction of composites, thus improving the mechanical properties of 3D braided composites and achieving practical modification effects while reducing the treatment cost 33 . At the same time, the composite matrix was modified and toughened.…”
Section: Introductionmentioning
confidence: 99%
“…CA/PGPA was oxidized, polymerized, and co-deposited on the surface of the fiber to introduce reactive groups on the fiber surface and improve the interfacial interaction of composites, thus improving the mechanical properties of 3D braided composites and achieving practical modification effects while reducing the treatment cost. 33 At the same time, the composite matrix was modified and toughened. Using aramid nanofibers (ANF) 34,35 and graphene nanoparticles (G) 36,37 to modify epoxy resin, the π-π interaction between ANF and G reduced the agglomeration phenomenon of nanofillers, which led to effective stress transfer, prevented crack extension in the matrix, and improved the mechanical properties of the 3D braided composites.…”
mentioning
confidence: 99%
“…Tu et al [ 17 ] constructed a polydopamine (PDA) functionalization platform and then deposited zinc oxide nanoparticles on the UHMWPE fiber surface and found that the interfacial adhesion with the rubber matrix was enhanced by 85.4%. Later, they [ 18 ] proposed a lower-cost surface modification strategy by replacing expensive dopamine with the catechol/tetraethylenepentamine two-component system.…”
Section: Introductionmentioning
confidence: 99%